Pancasila dan Hukum Konstitusi : Tinjauan Perkawinan Beda Agama di Indonesia : Pancasila and Constitutional Law: An Overview of Interfaith Marriages in Indonesia - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Saputra, Anggi; Musthofa Wahyu Pradana; Malika Yasifa Andika; Akhfal Nur Rohim (Litera Academica Publishing, 2024)
Interfaith marriage is a complex issue in Indonesia, especially when faced with the state ideology Pancasila and constitutional law. Pancasila, as the nation's ideology, prioritises the values of togetherness and harmony, while constitutional law in Law Number 1 Year 1974 on Marriage stipulates that a marriage is considered valid if it is conducted in accordance with the religious laws of each party. In practice, this raises various debates related to human rights, religious freedom, and state legal policy. The research method used is the Normative Juridical Approach method, this method focuses on the study of literature and legal regulations, such as the Anti-Terrorism Law in Indonesia. Researchers usually analyse legislative documents, legal theories, and how Pancasila values are applied in existing legal policies. The results of this study reveal that the role of Pancasila in making anti-terrorism legal policy in Indonesia shows that the philosophical idiological values of Pancasila serve as the foundation for the pol.